Effect of extracorporeal irradiation on segmental bone autograft incorporation in Sprague-Dawley rats (Faculty of Medicine Universitas Indonesia, 2014)
Background: Bone graft has been widely used in bone tumor reconstructive surgery. Extracorporeal irradiation (ECI) is commonly used to eliminate malignant cells before bone autograft. However, it may have negative effects on autograft incorporation. This study aimed to evaluate the ability of bone autograft incorporation after extra corporeal irradiation. Methods: 24 Sprague-Dawley rats underwent 7-mm en bloc resection of tibial diaphysis, and were divided into 4 groups. The first group did not receive irradiation; the 2nd, 3rd, and 4th groups received 50, 150 and 300 Gy bone irradiation respectively, and then reimplanted. Radiologic score were evaluated at week-6 and -8, while histopathology, osteoblast count and BMP-2 expression were examined at week-8. Data were analyzed with ANOVA or Kruskal-Wallis tests. Results: At week-6, radiologic scores in group 150 and 300 Gy were significantly lower compared to control group (4 vs 6 dan 4 vs 6; p = 0.011; p = 0.01). The same results were also obtained at week-8 (5.40 vs 7.14; p = 0.009 in the group 150 Gy and 5.60 vs 7.14; p = 0.018 in the group 300 Gy. Histopathological scores of the groups receiving 50, 150 and 300 Gy were significantly lower compared to the control group (6 vs 7, p = 0.017; 4 vs 7, p = 0.005; 6 vs 7, p = 0.013). Osteoblast count and BMP-2 expression were not significantly different among all groups. Conclusion: ECI with the dose of 50 to 300 Gy is associated with delayed bone autograft incorporation. However, the osteoinductive and osteogenesis capacity for autograft incorporation were maintained.